Environmental Drivers of Variation in Bleaching Severity of Acropora Species during an Extreme Thermal Anomaly - Hoogenboom, Mia O.; Frank, Grace E.; Chase, Tory J.; Jurriaans, Saskia; Álvarez-Noriega, Mariana; Peterson, Katie; Critchell, Kay; Berry, Kathryn L. E.; Nicolet, Katia J.; Ramsby, Blake; Paley, Allison S. (Frontiers in Marine Science, 2017)
High sea surface temperatures caused global coral bleaching during 2015-2016. During this thermal stress event, we quantified within- and among-species variability in bleaching severity for critical habitat-forming Acropora corals. The objective of this study was to understand the drivers of spatial and species-specific variation in the bleaching susceptibility of these corals, and to evaluate whether bleaching susceptibility under extreme thermal stress was consistent with that observed during less severe bleaching events. We surveyed and mapped Acropora corals at 10 sites (N = 596) around the Lizard Island group on the northern Great Barrier Reef. For each colony, bleaching severity was quantified using a new image analysis technique, and we assessed whether small-scale environmental variables (depth, microhabitat, competition intensity) and species traits (colony morphology, colony size, known symbiont clade association) explained variation in bleaching. Results showed that during severe thermal stress, bleaching of branching corals was linked to microhabitat features, and was more severe at reef edge compared with lagoonal sites. Bleaching severity worsened over a very short time-frame (~1 week), but did not differ systematically with water depth, competition intensity, or colony size. At our study location, within- and among-species variation in bleaching severity was relatively low compared to the level of variation reported in the literature. More broadly, our results indicate that variability in bleaching susceptibility during extreme thermal stress is not consistent with that observed during previous bleaching events that have ranged in severity among globally dispersed sites, with fewer species escaping bleaching during severe thermal stress. In addition, shaded microhabitats can provide a refuge from bleaching which provides further evidence of the importance of topographic complexity for maintaining the biodiversity and ecosystem functioning of coral reefs.